A Family of Lifetime Distributions. (13th May 2012) - Pappas, Vasileios; Adamidis, Konstantinos; Loukas, Sotirios
Abstract : A four-parameter family of Weibull distributions is introduced, as an example of a more general class created along the lines of Marshall and Olkin, 1997. Various properties of the distribution are explored and its usefulness in modelling real data is demonstrated using maximum likelihood estimates.